The CCCTB option: An experimental study - Claudia Keser; Gerrit Kimpel; Andreas Oestreicher (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
The objective of this paper is to look into the probability that, given the choice, corporate groups would opt for taxation on a consolidated basis. Consolidation would allow them to offset losses crossborder but remove the opportunity to exploit international tax-rate differentials between entities via transfer pricing. We present a laboratory experiment in which we investigate to what extent a corporation would be inclined to take up the consolidation option and how this would impact on the corporations location of investment and its transfer pricing activities involving locations outside the consolidated group. We use a 2-by-2 treatment design with two levels of tax-rate differential between two investment locations, and two different remuneration functions allowing the participants to act as owners or managers of a company.
Keywords: C91; H25; M41; 330; international company taxation; separate accounting; formula apportionment; transfer pricing; experimental economics